Three new Lepanthes species (Pleurothallidinae, Orchidaceae) from Ecuador - Thoerle, Lisa; Hirtz, Alexander C. (Phytotaxa, 2015)
The Ecuadorian Lepanthes calochroma, L. peltata, and L. spiculifera are proposed as new species, and are described, illustrated, and compared with the most similar species. A brief history and description of the genus are included. The flowers of L. calochroma are similar to those of L. golbasto, but the plant is larger and the flowers are brilliantly colored with petals with an upper lobe longer than the lower. The flowers of L. peltata have an unusual bladeless lip, resembling that of L. alticola, but the latter is distinguished by much larger flowers with long-acuminate sepals. Lepanthes spiculifera is distinguished from the similar L. zettleri by the unusual blunt-spiculate pedicel bearing smaller flowers with blunt-spiculate sepals, densely pubescent petals, and a lip with long-ciliate margins.